1998
DOI: 10.1002/(sici)1521-3765(19980615)4:6<1007::aid-chem1007>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Compounds with the Ir3Ge7 Structure Type: Interpenetrating Frameworks with Flexible Bonding Properties

Abstract: Reexamination of the E-rich (E Ga, In) area of the binary systems Ni/Ga and Pd/In yielded the stoichiometric compounds Ni 3 Ga 7 and Pd 3 In 7 with the Ir 3 Ge 7 structure type. The structure of the compounds was determined by single-crystal X-ray diffraction methods (space group Im3 Å m; Ni 3 Ga 7 : a 8.4285(6) , Pd 3 In 7 : a 9.4323(2) ; Z 4). The existence of the nonstoichiometric phases NiGa 4 and PdIn 3 reported earlier could not be confirmed and it is assumed that Ni 3 Ga 7 and Pd 3 In 7 represent the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(27 citation statements)
references
References 11 publications
0
27
0
Order By: Relevance
“…1 [7]. Below E F there is a rich structure but one recognizes two main regions, one spans just below E F down to 0.3 Ry, and the second region is located around 0.55 Ry, relative to E F .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 [7]. Below E F there is a rich structure but one recognizes two main regions, one spans just below E F down to 0.3 Ry, and the second region is located around 0.55 Ry, relative to E F .…”
Section: Resultsmentioning
confidence: 99%
“…Similarities and dierences between DOS of these compounds will be discussed in terms of their electronic and magnetic behaviour. Previously, a large number of theoretical investigations were dedicated to Mo 3 Sb 7 [58], while study on Ru 3 Sn 7 was reported only by Häussermann et al [7], who obtained from ab initio linear mun-tin orbital method in the atomic sphere approximation (ASA) calculations.…”
Section: Introductionmentioning
confidence: 99%
“…This is associated with a gap opened in the band structure, which separates the bonding and antibonding d ± pinteractions T7E. 150 Thus Nb 3 Sb 2 Te 5 and Mo 3 Sb 77x Te x (x & 2) exhibit semiconductor properties. Minor deviations from 55 are possible; in this case, the required concentration of charge carriers is achieved, thus optimising the thermoelectric properties.…”
Section: Polar Intermetallicsmentioning
confidence: 99%
“…[16][17][18][19][20][21] The matrix compound Mo 3 Sb 7 exhibits strong p-type metallic behavior because the Fermi level locates deep into the valence band. The effective way to optimize the electrical performance is to move the Fermi level towards the valence band maximum, which means more electrons are needed for this compound.…”
Section: Introductionmentioning
confidence: 99%